The accidental favorite : a novel [large type] - Littlewood, Fran (Thorndike Press large print dynamic drama., 2025)
"Vivienne and Patrick Fisher have done an excellent job raising their three daughters, Alex, Nancy, and Eva. They're well-adjusted women with impressive careers, caring partners, exciting hobbies, and sweet children. But when Patrick inadvertently reveals that he has a favorite daughter, no one is prepared for the shockwaves it sends through the family. Decades-old unresolved sibling rivalries are suddenly unmasked, and no secrets are safe, from ancient crushes to serious betrayals. Set over a single week, The Accidental Favorite is a compassionate, sharply observed portrait of the moments that shape a family through the years"--